Sociedad inclusiva: pensando en la inclusión de personas com discapacidad en la formación y en la vida - Machado, Clarita Franco de (Boletim Técnico do Senac, 2004)
This work discusses various practical challenges to building real inclusive education models, regarding education scope and quality, and its processes, products, and short- and long-term results. The insertion of people living with disabilities in life and work is viewed as an experience toward constructing inclusive social and educational institutions. To this extent, this work shows the advances and experiences of social insertion for people living with disabilities as part of building an inclusive society, presenting in its final section lessons learned from different contexts and countries to make educating for life and work a road to the social and economic inclusion of all citizens.